Communication and sport surveying the field - Billings, Andrew C.; Butterworth, Michael L.; Turman, Paul D. (SAGE, 2018)
Communication and Sport: surveying the field, third edition examines a wide array of topics necessary to understand sports media, rhetoric, culture, and organizations from micro- to macro-level issues. All levels of sports are addressed through varied lenses such as mythology, community, and identity. The third edition is newly expanded to incorporate the latest topics and perspectives in the field, including fan cultures, racial identity and gender in sports media, politics and nationality in sports, crisis communication in sports organizations, and more